Literary Genres and Ancient Philosophy - Gagin, François (Estudios de Filosofía, 2004)
There is an apparent correspondence between literary genres and the exercise of philosophy, but what is it? If we remember the a-typicality of the philosopher in search of a meaning that orients life, we understand there is no exclusive literary genre for the exercise of philosophy. The Greek way of philosophizing can fit both a hymn's or anepistle's structure. No genre is exclusive to a philosophical experience because in order to understand this experience it's necessary to reveal first a negative definition of what is not; such experience does not consist in provoking meaninglessness or loss of meaning and, there isn't in Antiquity an exercise of literature suitable for the cult of ugliness or for an opening to wrong. Chaos or hubris does not belong in the realm of what’s arguable and philosophy opposes values that are not the true values. After the place of uncertainty where the philosopher positions himself, in this tension between doxa and episteme, the fundamental choice of life comes, and this is what determines, in turn, the choice of one literary genre or another. The fundamental choice of life actually is a school ofeducation and the discourse that shapes it mustfully correspond with it. Thus the almost exclusive choice of this or that literary genre in this or that school is explained. The above can serve as an example to apprehend Cleanthes' Hymn to Zeus.